EFL JUNIOR HIGH SCHOOL TEACHERS’ PERCEPTION ON THE IMPLEMENTATION OF STUDENT-CENTERED LEARNING MODELS IN THE ENGLISH LESSON BASED ON THE 2013 CURRICULUM - Desak Gede Devi Pratami; I Putu Ngurah Wage Myartawan; Dewa Ayu Eka Agustini (Universitas Pendidikan Ganesha, 2022)
This study aimed to investigate EFL Junior High School Teachers’ Perception on the Implementation of Student-Centered Learning Models in the English Leaaon based on the 2013 Curriculum. This study employed a quantitative research design with used survey. The sample of this study are all of EFL Junior High School Teachers in 11 schools in Tabanan town, total 21 teachers. The data were collected by using questionnaire in which this study is close-ended and analyzed descriptively. The questionnaire used five-point likert scale to measure the level of response from the statements, namely; 1 (Strongly disagree), 2 (Disagree), 3 (Neutral), 4 (Agree), 5 (Strongly agree). The result showed that a lot of Teachers in Tabanan give positif response.